A Randomized Trial of Continuous Versus Intermittent Skin-to-Skin Contact After Premature Birth and the Effects on Mother–Infant Interaction. (June 2020) - Sahlén Helmer, Charlotte; Birberg Thornberg, Ulrika; Frostell, Anneli; Örtenstrand, Annica; Mörelius, Evalotte
Abstract : Background: Premature birth affects opportunities for interaction between infants and mothers. Skin-to-skin contact (SSC) is standard care in neonatal care but has not been sufficiently studied regarding the effects on interaction between preterm infant and mothers. Purpose: The purpose of this study was to compare interaction between preterm infants and their mothers after continuous versus intermittent SSC from birth to discharge. A secondary aim was to study a potential dose–response effect between time in SSC and quality of interaction. Methods: Families were randomly assigned to either continuous (n = 17) or intermittent (n = 14) SSC before delivery. Interaction was measured from videotapes of a Still-Face Paradigm collected at 4 months' corrected age. Face-to-face interaction was coded according to Ainsworth's Maternal Sensitivity Scales and the Maternal Sensitivity and Responsivity Scales-R. Dose–response correlations were calculated between mean time spent in SSC and each of the interaction scales. Results: There were no statistically significant differences between groups in maternal interactive behavior toward their infants regarding sensitivity, interference, availability, acceptance, withdrawal, or intrusivity. There was no correlation between mean time in SSC and quality of interaction. Implications for Practice: Continuous SSC from birth to discharge was not superior to intermittent SSC concerning mother–infant interaction between preterm infants and their mothers at 4 months' corrected age. However, compared with other studies, mean time in SSC was also high in the intermittent group. Implications for Research: Further studies are needed to find out how interaction between parents and preterm infants can be improved, supported, and facilitated in the neonatal intensive care unit (NICU) and whether there is an optimal dose for SSC.